Las Destrezas de Comunicación del Director Escolar y el Manejo de Conflicto en Puerto Rico - Alma Y. Castilloveitía (Universidad Autónoma de Madrid, 2017)
The present research study the communication skills of the school director and conflict management in the middle schools of two school districts of the Department of Education of Puerto Rico. The research was carried out using a descriptive correlational design. According to theresults it was determined that there is no significant relationship between the communication skills of the school director and the total number of conflicts resolved in the school site. According to the findings, the communication skills that the participating school principals use in the conflict mediation process are: To inform about the conflict to be addressed, to inform the truth about the conflict to be treated between the parties involved in the dissolution process of The conflicts in their schools and evaluate the positive and negative effects to carry out the conclusion of the conflict in their schools. Other communication skills used by participating school principals according to the findings are: to verify the negative traits, to consider the truth of the conflict data, before being a mediator and to know the parties involved and to establish agreements on an equal basis to cause The dissolution of the conflict in their respective schools.